Efficient sampling of shiitake-inoculated oak logs to determine the log-to-mushroom transfer factor of stable cesium - Martin O’Brien; Masakazu Hiraide; Yoshimi Ohmae; Naoto Nihei; Satoru Miura; Keitaro Tanoi (PeerJ, 2019)
Background Stable cesium (133Cs) naturally exists in the environment whereas recently deposited radionuclides (e.g., 137Cs) are not at equilibrium. Stable cesium has been used to understand the long-term behavior of radionuclides in plants, trees and mushrooms. We are interested in using 133Cs to predict the future transfer factor (TF) of radiocesium from contaminated logs to shiitake mushrooms in Eastern Japan. However, the current methodology to obtain a representative wood sample for 133Cs analysis involves mechanically breaking and milling the entire log (excluding bark) to a powder prior to analysis. In the current study, we investigated if sawdust obtained from cutting a log along its length at eight points is as robust but a faster alternative to provide a representative wood sample to determine the TF of 133Cs between logs and shiitake. Methods Oak logs with ready-to-harvest shiitake fruiting bodies were cut into nine 10-cm discs and each disc was separated into bark, sapwood and heartwood and the concentration of 133Cs was measured in the bark, sapwood, heartwood, sawdust (generated from cutting each disc) and fruiting bodies (collected separately from each disc), and the wood-to-shiitake TF was calculated. Results We found that the sawdust-to-shiitake TF of 133Cs did not differ (P = 0.223) compared to either the sapwood-to-shiitake TF or heartwood-to-shiitake TF, but bark did have a higher concentration of 133Cs (P < 0.05) compared to sapwood and heartwood. Stable cesium concentration in sawdust and fruiting bodies collected along the length of the logs did not differ (P > 0.05). Discussion Sawdust can be used as an alternative to determine the log-to-shiitake TF of 133Cs. To satisfy the goals of different studies and professionals, we have described two sampling methodologies (Methods I and II) in this paper. In Method I, a composite of eight sawdust samples collected from a log can be used to provide a representative whole-log sample (i.e., wood and bark), whereas Method II allows for the simultaneous sampling of two sets of sawdust samples—one set representing the whole log and the other representing wood only. Both methodologies can greatly reduce the time required for sample collection and preparation.